Amputation lower limb due to Diabetes Mellitus the states and regions of Brazil (Research, Society and Development, 2021)
Amputation due to Diabetes Mellitus consists of a worldwide dimension of severity, frequently occurring in populations of low socioeconomic status in inadequate conditions of hygiene and lack of access to health facilities. The diabetic foot is associated with factors such as diabetic neuropathy, peripheral arterial disease and infection, contributing to a prognosis of ulceration and / or necrosis in the finger, part of the foot, complete foot and / or leg, amputation and death. The aim of this study was to determine the epidemiological profile of amputation in lower limbs due to diabetes mellitus in the regions and states of Brazil. The research was carried out through the databases of the Registry of lower limb amputation procedures in the Hospital Information System (SIH / SUS) for the period from 2000 to 2020. Amputation was more prevalent in the southeast, northeast, south, respectively. midwest and north. The findings of this study also indicate the need for early promotion of screening, diagnosis, treatment, rehabilitation, in order to enhance healing and return to activities of daily and professional life, avoiding amputation and death.